Sorption behaviors of tris-(2, 3-dibromopropyl) isocyanurate and hexabromocyclododecanes on polypropylene microplastics. (October 2018) - Liu, Xiaowen; Zheng, Minggang; Wang, Ling; Ke, Runhui; Lou, Yinghua; Zhang, Xiaojun; Dong, Xiaofeng; Zhang, Yu
Abstract: In recent years, microplastics in oceans have become a serious environmental problem and the focus of attention. In the present study, the sorption of TBC and HBCDs by microplastics in simulated seawater is examined. The effects of particle size, temperature, salinity, and concentration on the adsorption of TBC and HBCDs by microplastics are studied. Results indicate that the first-order adsorption kinetic model is more suitable than the pseudo-second-order kinetic model to describe adsorption. The equilibrium adsorption times are 15 h and 10 h for TBC and HBCDs, respectively. The adsorption capacity increases with the decrease in particle size. The adsorption capacity gradually increases at first and then decreases with the increase in salinity and temperature. The maximum adsorption capacity is at 15 °C and 14% salinity. Compared with the linear and Freundlich models, the Langmuir model is more suitable; this indicates that the main adsorption mechanism might be chemical adsorption. Highlights: The influence of microplastics, TBC and HBDs on marine environment, has become a focus issue. First-order adsorption kinetic model is more suitable to describe the adsorption than pseudo-second-order kinetic model. Compared with linear and Freundlich model, Langmuir model is more suitable to describe the adsortion. Understanding the interaction between TBC, HBCDs and microplastics is essential for investigating the impacts on environment.